The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1128/jvi.03799-13
|View full text |Cite
|
Sign up to set email alerts
|

TMPRSS2 Is a Host Factor That Is Essential for Pneumotropism and Pathogenicity of H7N9 Influenza A Virus in Mice

Abstract: Cleavage of the hemagglutinin (HA) by host proteases is essential for the infectivity of influenza viruses. Here, we analyzed the role of the serine protease TMPRSS2, which activates HA in the human respiratory tract, in pathogenesis in a mouse model. Replication of the human H7N9 isolate A/Anhui/1/13 and of human H1N1 and H3N2 viruses was compared in TMPRSS2 knockout (TMPRSS2 ؊/؊ ) and wild-type (WT) mice. Knockout of TMPRSS2 expression inhibited H7N9 influenza virus replication in explants of murine tracheas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

12
148
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 131 publications
(160 citation statements)
references
References 49 publications
12
148
0
Order By: Relevance
“…TMPRSS2 appears to be essential for influenza H1N1 virus to be pathogenic in mice but not for H3N2 virus pathogenicity (9). H1N1 virus replication was suppressed in the respiratory tract of TMPRSS2 Ϫ/Ϫ mice, while H3N2 virus replication was only marginally affected (11). It was recently proposed that TMPRSS4 plus TMPRSS2 activate H3N2 viruses in mice (12).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…TMPRSS2 appears to be essential for influenza H1N1 virus to be pathogenic in mice but not for H3N2 virus pathogenicity (9). H1N1 virus replication was suppressed in the respiratory tract of TMPRSS2 Ϫ/Ϫ mice, while H3N2 virus replication was only marginally affected (11). It was recently proposed that TMPRSS4 plus TMPRSS2 activate H3N2 viruses in mice (12).…”
Section: Discussionmentioning
confidence: 99%
“…Although TMPRSS2 is a marker of susceptibility to severe A (H1N1)pdm09 influenza virus (8), there is no clinical data indicating the involvement of a specific protease in the activation of seasonal IAV. However, in mice, TMPRSS2 has been identified as being essential for the spread of H1N1 IAV (9)(10)(11) and of H3N2 IAV in association with TMPRSS4 (12).…”
mentioning
confidence: 99%
“…It was previously shown that TMPRSS2 allows HA cleavage thus promoting viral spread. Knockout of TMPRSS2 could prevent the propagation of H1N1, H7N9 viruses into the lungs of mice, however, TMPRSS2 seemed to play only marginal role in H3N2-caused infection 23,24 .…”
Section: Discussionmentioning
confidence: 99%
“…Our group (1) and Hatesuer et al (2) showed that TMPRSS2 is essential for proteolytic activation of both H1N1 and H3N2 subtype IAVs. However, Tarnow et al (3) reported that TMPRSS2 is not critical for activation of H3N2 IAV. Since the three groups used different H3N2 IAV strains, the discrepancy likely arose from possible variations in HA among the H3N2 IAV strains.…”
mentioning
confidence: 99%
“…Using mouse models, three research groups recently demonstrated that a type II transmembrane serine protease, TMPRSS2, expressed in the airway epithelium, is critically important for HA cleavage in vivo (1)(2)(3). Mice lacking TMPRSS2 expression (TMPRSS2 knockout [tmprss2 KO ] mice) are highly tolerant of challenge infection by low-pathogenic (LP) IAVs possessing a monobasic cleavage site in HA.…”
mentioning
confidence: 99%